The development dimension of an investment facilitation framework - Khalil Hamdani (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2020)
The development dimension of the WTO discussions on investment facilitation includes provisions on special and differential treatment and technical assistance for developing countries. Also important are corporate responsibility and home country support of host country measures. The discussions should ensure that these development provisions are more than hortatory language.
Keywords: 330